Gastric Endometriosis (Central Asian Journal of Medical Sciences, 2017)
Objectives: First reported in 1950, endometriosis is characterized by the presence of endometrial glands and stroma outside the endometrial cavity. Methods: A forty year old Mongolian woman had symptoms of epigastric and right upper quadrant pain, slow digestion, early satiety, and occasional diarrhea when diagnosed with gastroptosis in 2014. In December 2016, her symptoms became more severe and, at times, dry food would become stuck in her throat. Results: The patient was successfully treated by surgery and has not shown evidence of recurrence, although prolonged observation is necessary. Conclusion: The treatment of choice for extrapelvic endometriosis is surgical resection.